Nursing of a patient with multiple valvular heart disease treated by extracorporeal membrane oxygenation combined with continuous renal replacement therapy after emergency redo thoracotomy (1例联合瓣膜病患者紧急二次开胸后实施ECMO联合CRRT救治的护理) - XU Jiajia (徐佳佳); SU Yunyan (苏云艳); WU Mengya (伍梦雅) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of a patient with multiple valvular heart disease treated by extracorporeal membrane oxygenation (ECMO) combined with continuous renal replacement therapy (CRRT)after emergency redo thoracotomy. Key points of nursing included observation on vital signs, cardiac function maintenance, ECMO-related care, airway management and CRRT-related care. (本文总结1例重症联合瓣膜病患者术后紧急二次开胸后行体外膜肺氧合(ECMO)联合连续肾脏替代疗法(CRRT)救治的护理体会, 包括生命体征的监测、心功能维护、ECMO护理、气道护理、CRRT护理等, 通过严密的护理措施, 以确保患者得到有效救治。)